Auction Design, Incentives, and Buying Back Maryland and Virginia Crab Licenses. (3rd May 2013) - DePiper, Geret S.; Higgins, Nathaniel; Lipton, Douglas W.; Stocking, Andrew
<x xml:space="preserve">Abstract</x> Fisheries managers use buybacks to reduce fleet capacity, conserve fish stocks, and accomplish other goals. In 2009, Maryland and Virginia conducted auctions to buy back commercial fishing licenses. The auctions in both States had similar timing, objectives, and target populations. The divergent designs of the auctions, however, provide a case study with which to investigate effective buyback practices. We compare and contrast the market designs used by Maryland and Virginia, and describe how those differing designs influenced the respective outcomes.